PERANCANGAN APLIKASI ABSENSI PESERTA MAGANG BERBASIS ANDROID MENGGUNAKAN JARINGAN INTRANET - Haris Tehuayo (Lembaga Pengembangan Kinerja Dosen, 2023)
Attendance is an activity in making data to find out the number of attendance at an activity. Data collection on attendance of apprentices at the Manpower Office of South Sulawesi Province still uses the manual method, namely in paper form by using a signature. It is found that there are many shortcomings, namely attendance data will be easily damaged and lost, so that data processing becomes less effective. The purpose of the research is to design an Androidbased internship attendance application using an intranet network to monitor the attendance, permits and daily activities of interns during working hours. This research is qualitative in nature by digging information on interns and intranet networks under investigation by making direct observations to the research location, can be tested and produce an expected application. The method of testing the black-box system, namely checking the feasibility and quality of using the application, has been functioning properly or not. The results of application testing, the user logs in with username and password verification to enter the main menu. The user (supervisor) inputs permission, sees the history of attendance and activities, while the user (internship participant) accesses the entry and exit attendance display. The conclusion of the application shows that the input and output functionalities generally run well, providing easy access to the attendance recap compared to the manual system currently used.